The relationship between the perception of the companyand employee attitude in the context of CSR – the results of the empirical study - Stefańska, Magdalena (Research Papers of Wrocław University of Economics, 2018)
The considerations in this article address the issue of the relationship between the perception of the organization and the attitude of employees from the perspective of the employer’s activities in the area of social responsibility. Several conclusions were made, based on both literature studies and empirical studies conducted among the employees of trade companies. Firstly, the existence of a connection between the perception of the employer and the level of their involvement in CSR activities was confirmed. The relationship between the perception of the organization and the influence of the immediate manager on this evaluation was also indicated. However, no relationship was found between the selected proenvironmental activities of the employee undertaken on a personal level, and their level of involvement in the workplace, or their perception of the employer
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2018; Nr 520; s. 136-149
Keywords: CSR; employees engagement; perception of the employer; trade organizations; zaangażowanie pracowników; postrzeganie pracodawcy; sieci handlowe